THE EFFECT OF MNEMONIC LOCI TECHNIQUE ON STUDENTS’ VOCABULARY MEMORIZATION - Iwan Kurniarahman (Language-Edu, 2020)
This current study reports the effect of mnemonic loci technique on students’ vocabulary memorization. Being designed in quasi-experimental, the study answered these two questions: (1) Is there any significant difference in short-term retention of vocabulary items between the students of the mnemonic loci technique and the students of the repetition technique?, and (2) Is there any significant difference in long-term retention of vocabulary items between the students of the mnemonic loci technique and students of the repetition technique? The samples were 50 students taken from two classes, i.e. class XI of Social Science (27 students in experimental group) and class XI of Natural Science (23 students in control group). Two posttests were administered to obtain the posttest data which were analyzed using Independent T-test. The immediate posttest revealed that the t-observed was 1.134. This t-observed had the Sig. (2-tailed) of .262 which was much higher than .05. Since the Sig. (2-tailed) was much higher than .05, it led to the conclusion that both groups showed the same performance. Further, the delayed posttest revealed that the t-observed was 2.551. This t-observed had the Sig. (2-tailed) of .014. Since the Sig. (2-tailed) was below .05, the experimental group outperformed the control group.